Synthesis of 1,2,4-Oxadiazoles Based on Diffractaic Acid - Aleksandr Filimonov; Anastasia Diveikina; Yuri Gatilov; Olga Luzina; Nariman Salakhutdinov (Molbank)
Diffractic acid 1 is a secondary metabolite of depside lichens with antibacterial and insecticidal properties, and anticancer, hepatoprotective and antiviral activities. Novel diffractaic acid derivatives containing a 1,2,4-oxadiazole ring with an aryl substituent have been synthesized by the reaction of diffractaic acid with amidoximes.